The Impact of Supplementing Probiotics and Concentrate on Intake, Nutrient Digestibility, and Nitrogen Balance in Sahelian Goats Fed a Basal Diet of Brachiaria Decumbens Grass: The Impact of Supplementing Probiotics (Journal of Science and Technology, 2025)
Four Sahelian bucks aged 24-26 months with a mean weight of 18.86±0.06 kg fed Brachiaria decumbens grass as a basal diet were used to investigate the supplementation effects of probiotics and concentrates relative to feed intake, nutrient digestibility, as well as nitrogen utilisation. The bucks were arranged in a 4 × 4 repeated Latin Square Design, consisting of four periods, each lasting 14 days. All bucks were adjusted to the test diets and handling conditions in metabolism cages for 2 weeks. The test diets consisted of P0 C500 (500 g/d concentrate without probiotics), P0 C1000 (1000 g/d concentrate without probiotics), P100C500 (probiotics at 100 g/100 kg of concentrate, 500 g/d concentrate), and P100C1000 (probiotics at 100 g/100 kg of concentrate, 1000 g/d concentrate). Throughout the experiment, the bucks had unfettered access to water and feed. Total amounts of urine and faeces were gathered during the final 7 days of each period for computation of nitrogen balance. Analysed results indicated that intake of basal diet was not affected (P > 0.05) by treatments imposed. However, increases (P< 0.05) in intake of water, total dry matter, and apparent digestibility of all nutrients except ash, nitrogen-free extract, and cellulose wereobserved. Nonetheless, nitrogen intake, digestibility, and retention in bucks on treatments P0 C1000 and P100C1000 were higher (P